2021
DOI: 10.3390/app11178013
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation of Reference Evapotranspiration and Its Climatic Drivers over the Tibetan Plateau during 1970–2018

Abstract: Reference evapotranspiration (ET0) is a key component of hydrologic cycle and it is important for water resources management. Analysis of ET0 changes is particularly critical for understanding the impacts of climatic change on hydrology in ecologically fragile regions. In this study, using the Penman–Monteith method and the Mann–Kendall test, the variation characteristics of ET0 on the Tibetan Plateau (TP) from 1970 to 2018 was analyzed, and the dominant climatic factors controlling the change of ET0 was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…ET 0 experienced an increasing trend with the rate of 0.33 mmÁyear −1 during 1960-2017, although it showed an upward-downward-upward trend with changing points of 1973 and 1993. This is similar to a previous study (Wang et al, 2013) but different from other studies (Zhang et al, 2009;Xie and Zhu, 2013;Hu et al, 2021;Liu et al, 2021). Wang et al (2013) found that ET 0 presented a zigzag (increasingdecreasing-increasing) pattern with two joint points (1973 and 1993), while no significant trend was observed during the entire period of 1961-2010.…”
Section: Contributions Of Variations Of Climatic Variables To the Var...supporting
confidence: 65%
See 4 more Smart Citations
“…ET 0 experienced an increasing trend with the rate of 0.33 mmÁyear −1 during 1960-2017, although it showed an upward-downward-upward trend with changing points of 1973 and 1993. This is similar to a previous study (Wang et al, 2013) but different from other studies (Zhang et al, 2009;Xie and Zhu, 2013;Hu et al, 2021;Liu et al, 2021). Wang et al (2013) found that ET 0 presented a zigzag (increasingdecreasing-increasing) pattern with two joint points (1973 and 1993), while no significant trend was observed during the entire period of 1961-2010.…”
Section: Contributions Of Variations Of Climatic Variables To the Var...supporting
confidence: 65%
“…Xie and Zhu (2013) indicated that ET 0 on the TP showed an obvious decreasing trend from 1970 to 2009. Zhang et al (2009) indicated that ET 0 decreased in most regions of the TP on annual and seasonal scales during 1970-2004. Hu et al (2021 reported that annual ET 0 showed an insignificant decreasing trend with the abrupt change in 1997 during 1970-2018.…”
Section: Contributions Of Variations Of Climatic Variables To the Var...mentioning
confidence: 98%
See 3 more Smart Citations